Improved diagnosis of gastrointestinal infections using a semi-automated multiplex real-time PCR for detection of enteropathogens. Issue 9 (13th September 2021) - Fidalgo, Berta; Rubio, Elisa; Pastor, Victor; Parera, Marta; Ballesté-Delpierre, Clara; Fernández, Mariana José; Chasco, Genoveva Cuesta; Vergara, Andrea; Zboromyrska, Yuliya; Aylagas, Cristian; Salvador, Pilar; Fernández, Adán; et al.
Abstract : Introduction. The identification of enteropathogens is critical for the clinical management of patients with suspected gastrointestinal infection. The FLOW multiplex PCR system (FMPS) is a semi-automated platform (FLOW System, Roche) for multiplex real-time PCR analysis. Hypothesis/Gap Statement. FMPS has greater sensitivity for the detection of enteric pathogens than standard methods such as culture, biochemical identification, immunochromatography or microscopic examination. Aim. The diagnostic performance of the FMPS was evaluated and compared to that of traditional microbiological procedures. Methodology. A total of 10 659 samples were collected and analysed over a period of 7 years. From 2013 to 2018 (every July to September), samples were processed using standard microbiological culture methods. In 2019, the FMPS was implemented using real-time PCR to detect the following enteropathogens: Shigella spp., Salmonella spp., Campylobacter spp., Giardia intestinalis, Entamoeba histolytica, Blastocystis hominis, Cryptosporidum spp., Dientamoeba fragilis, adenovirus, norovirus and rotavirus. Standard microbiological culture methods (2013–2018) included stool culture, microscopy and immunochromatography. Results. A total of 1078 stool samples were analysed prospectively using the FMPS from July to September (2019): bacterial, parasitic and viral pathogens were identified in 15.3, 9.71 and 5.29 % of cases, respectively. During the same period of 6 years (2013–2018), the proportion of positive identifications using standard microbiological methods from 2013 to 2018 was significantly lower. A major significant recovery improvement was observed for all bacteria species tested: Shigella spp./enteroinvasive Escherichia coli (EIEC) ( P <0.05), Salmonella spp. ( P <0.05) and Campylobacter spp. ( P <0.05). Marked differences were also observed for the parasites G. intestinalis, Cryptosporidium spp. and D. fragilis . Conclusion. These results support the value of multiplex real-time PCR analysis for the detection of enteric pathogens in laboratory diagnosis with outstanding performance in identifying labile micro-organisms. The identification of unsuspected micro-organisms for less specific clinical presentations may also impact on clinical practice and help optimize patient management.